Redesain Ruang Ibadah Masjid Agung Pati Berdasarkan Performa Kenyamanan Termal, Visual, Dan Akustik - furqoni, ashim; Prianto, Eddy; Sardjono, Agung Budi; Hardiman, Gagoek (RUAS, 2022)
Architecture is a place to move comfortably. The mosque is the four worshippers of muslims who should have an optimal level of comfort. This study aims to examine the comfort performance of the prayer room of the Great Mosque of Pati based on applicable theories and standards, then design based on the results of a comfort study to get a prayer room design that meets the comfort criteria for its users. The research was conducted by dividing the prayer room into 16 points. At each point, 3 measurements are carried out, namely thermal, lighting, and noise measurements both in the morning, afternoon, afternoon, and evening. From the measurement results, it is known that the average temperature in the worship room is 27.4 Â°C, meaning that the temperature is hotter than the standard of comfort (<27 Â°C). The average exposure is 103.5 lux, meaning the lighting is darker than required (200 lux). The average noise is 61.7 dB, meaning that the situation inside the worship room is noisier than the maximum noise level allowed for the worship space (55 dB).